Hubungan Umur dan Gravida dengan Kekurangan Energi Kronik pada Ibu Hamil di Puskesmas Pagar Merbau - Asmiati Boru Purba; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Rahmah Rahmah (PPNI UNIMMAN, 2024)
Nutrition plays an important role in influencing health, especially in pregnant women. Adequate nutritional intake is very important to support the health of the mother and fetus. Malnutrition, such as Chronic Energy Deficiency (CED), is a health problem that is often experienced by pregnant women. This study aims to analyze the relationship between age and number of pregnancies (gravida) with the incidence of CED in pregnant women at the Pagar Merbau Health Center, Pagar Merbau District, Deli Serdang Regency, in 2023. This study used an analytical design with a cross-sectional approach, which observed independent and dependent variables only once at a time. The study sample consisted of 56 pregnant women selected using the Purposive Sampling technique. The results showed that most respondents had a high school education of 34 people (60.7%), with the least number of college graduates of 2 people (3.6%). Most respondents were unemployed or housewives as many as 30 people (53.6%), while those who worked as farmers, employees, traders, and laborers were 10 people (10%), 8 people (14.3%), 7 people (12.5%), and 1 person (1.8%). This study also shows that the more often a mother is pregnant, the less attention she pays to health and nutritional intake, because pregnancy is considered a common thing.